Gender bias and ‘doctor brides’. A social dilemma of medical students in Pakistan - Ashraf , Mohammad; Cheema, Huzaifa Ahmad; Farooq, Minaam; Mustafa, Biah; Anwer, Ammar; Shahid, Saman; Ashraf, Naveed (Journal of the Pakistan Medical Association, 2023)
Objective: To assess gender bias, discrimination and bullying at medical schools, and to explore the phenomenon of ‘doctor brides’. Method: The multicentre survey was conducted at 14 medical education institutions across Pakistan from September 2020 to April 2021, and comprised medical students of either gender at both public-sector and private-sector institutions. The survey questions explored beliefs, experiences and knowledge related to common stereotypes and social issues in medical education, including female role models, work-life balance, gender roles, lack of support from family and faculty, and bullying. Association between gender with survey variables was explored. Data was analysed using SPSS 26. Thematic analysis was used to exploring knowledge around ‘doctor-brides’. Results: Of the 377 subjects, 245(65%) were females. The overall mean age was 21.4+/- 1.8 years. There were 211(53.8%) subjects aged 21-23 years, and 368(97.6%) were Muslims. Significantly more women than men were of the opinion that men are encouraged and are more likely to assume leadership roles (p=0.002). More women than males agreed that household chores and work had an impact on speciality choice (p<0.001). Most sexual assault victims were women (p<0.0001), but men generally faced more bullying and hostile behaviour (p=0.014). With regard to women being forced to quit medicine after marriage/childbirth by their in-laws/husbands or change their careers from clinical medicine to preclinical teaching, 99(26.25%) subjects knew first-hand of such cases, while 238(63.12%) had no such experience to share. Conclusion: Gender bias, discriminatory behaviour and bullying were found to be widely prevalent in medical schools across Pakistan. The general perception of ‘doctor brides’ needs to be revisited. Key Words: Gender bias, Bullying, Doctor brides, Medical students, Pakistan.